The impact of electrode with carbon materials on safety performance of lithium-ion batteries: A review. (May 2022) - Jiang, Xiaomei; Chen, Yanjun; Meng, Xiaokai; Cao, Weiguo; Liu, Changcheng; Huang, Que; Naik, Nithesh; Murugadoss, Vignesh; Huang, Mina; Guo, Zhanhu
Abstract: Along with the wide application of lithium-ion batteries (LIBs), the fire accidents also occur frequently, causing unimaginable losses of life and property. Thermal runaway (TR) is the main reason for LIB fire and explosion, in which carbon materials play an important role. Therefore, this review presents the information about the influence of carbon materials on the safety of LIBs. In the first place, the effects of carbon materials as electrodes on battery safety performance and electrochemical properties were summarized. Subsequently, the roles of each component during TR and the process were introduced, the importance of carbon materials was highlighted. Finally, the improvement measures of carbon electrode materials were summarized, and their influence mechanism on the safety of LIBs was reviewed. By understanding the importance of carbon materials in the TR processing and comparing the advantages and disadvantages, it is concluded that the presently widely used carbon materials have significant impacts on the thermal hazard of batteries. Graphical abstract: Image 1 Highlights: The applications of carbon materials in lithium-ion batteries were systematically described. The mechanism of typical combustibles inside battery, especially electrode on the safety performance is clarified. The methods to improve the thermal stability of batteries with graphite is summarized. Existing fire risk problems and the solutions for carbon anodes are discussed.